ВПЛИВ КОРОННОГО РОЗРЯДУ НА КРАТНІСТЬ ВНУТРІШНІХ ПЕРЕНАПРУГ У МАГІСТРАЛЬНИХ ЕЛЕКТРИЧНИХ МЕРЕЖАХ - Кузнецов , В.Г.; Тугай , Ю.І.; Кучанський , В.В. (Інститут електродинаміки НАН України, Київ, 2017)
The conditions of development resonance overvoltages in abnormal modes of electrical networks have been studied. Investigations of changing overvoltages on cycle single phase auto reclose in extra high voltage transmission line have been implemented by simulation modeling. Equivalent scheme of resonance circuit with parameters of corona discharge have been composed. The analytical dependencies of line’s length in which there have been observed maximum value overvoltages on disconnecting phase have been obtained. Influence of corona discharge on resonance overvoltages in open-phase modes real extra high voltage transmission lines have been investigated. Values of resonance overvoltages and characteristic of line have been obtained by express-method and simulation modeling. The factors which most of all influence on occurrence resonance overvoltages have been identified by using express-method with detecting resonance length of the line. Verification of results which have been obtained by imitation model with result of field experiments has been implemented. References 11, figures 4, table 1.